Orbital frustration in the S = ½ kagome magnet vesignieite, BaCu3V2O8(OH)2. Issue 43 (24th October 2016) - Boldrin, David; Knight, Kevin; Wills, Andrew S.
Abstract : Here we report crystallographic and magnetic studies on high quality samples of the magnetically frustrated S = ½ kagome antiferromagnet vesignieite, BaCu3 V2 O8 (OD)2 . Abstract : Here we report crystallographic and magnetic studies on high quality samples of the magnetically frustrated S = ½ kagome antiferromagnet vesignieite, BaCu3 V2 O8 (OD)2 . Powder neutron diffraction data collected from samples obtained by a new hydrothermal synthetic route reveal a previously unobserved trigonal P 31 21 structure, similar to the isoelectronic mineral SrCu3 V2 O8 (OH)2 . The refined structure is consistent with orbital frustration of the eg d-orbitals in a sublattice of the Cu 2+ kagome network due to a dynamic Jahn–Teller effect, which persists below the magnetic transition at T N = 9 K and makes the material an interesting candidate for exploring concomitant spin and orbital frustration. A combination of crystallographic strain analysis and magnetisation measurements indicate strong magnetostructural coupling which may explain the varied magnetic behaviour between samples of vesignieite in the literature. The revised orbital structure is similar to that found in volborthite, rather than the quantum spin liquid herbertsmithite, and provides a convincing argument for the differing magnetic properties found in these frustrated magnets.